Review paper: Instrumentation for marine magnetotelluric and controlled source electromagnetic sounding. (29th January 2013) - Constable, Steven
ABSTRACT: We review and describe the electromagnetic transmitters and receivers used to carry out magnetotelluric and controlled source soundings in the marine environment. Academic studies using marine electromagnetic methods started in the 1970s but during the last decade these methods have been used extensively by the offshore hydrocarbon exploration industry. The principal sensors (magnetometers and non‐polarizing electrodes) are similar to those used on land but magnetotelluric field strengths are not only much smaller on the deep sea‐floor but also fall off more rapidly with increasing frequency. As a result, magnetotelluric signals approach the noise floor of electric field and induction coil sensors (0.1 nV/m and 0.1 pT) at around 1 Hz in typical continental shelf environments. Fluxgate magnetometers have higher noise than induction coils at periods shorter than 500 s but can still be used to collect sea‐floor magnetotelluric data down to 40–100 s. Controlled source transmitters using electric dipoles can be towed continuously through the seawater or on the sea‐bed, achieving output currents of 1000 A or more, limited by the conductivity of seawater and the power that can be transmitted down the cables used to tow the devices behind a ship. The maximum source‐receiver separation achieved in controlled source soundings depends on both the transmitter dipole moment and on the receiver noise floor and is typically around 10 km in continental shelf exploration environments. The position of both receivers and transmitters needs to be navigated using either long baseline or short baseline acoustic ranging, while sea‐floor receivers need additional measurements of orientations from compasses and tiltmeters. All equipment has to be packaged to accommodate the high pressure (up to 40 MPa) and corrosive properties of seawater. Usually receiver instruments are self‐contained, battery powered and have highly accurate clocks for timekeeping, even when towed on the sea‐floor or in the water column behind a transmitter.